Structural Properties of Liquid CaO–SiO2–P2O5 System - Anh, Nguyen Mai; Van Hong, Nguyen (VNU Journal of Science: Mathematics - Physics, 2023)
Crystalline structure of CaO-P 2 O 5 -SiO 2 system at 3,000 K were investigated by molecular dynamic simulation. The models with different concentrations of P 2 O 5 (5-40 mol%) were constructed by using Born-Mayer-Huggins potentials. The size of models was from 5,270-5,520 atoms. The local environment of elements and glassy-network structure were investigated in detail. The radial distribution functions (RDFs) showed that the average first nearest neighbor distances for Ca-O, P-O and Si-O were of 2.28-2.3Å, 1.56-1.58Å and 1.64-1.68Å, respectively. The BO fraction increases and NBO ratio decreases with the uptrend of the concentration of P 2 O 5 . The change of P 2 O 5 content also changes the structures of [SiO4] and [PO4] tetrahedrons clusters.